Effects of a Cinnamon, Curcumin/Turmeric Dietary Supplement on Glucose, Lipid, and Cognitive Measures - Young, Hayley; Clayton, Diane; Masis, Natalie; Gaylor, Chantelle; Benton, David (Current developments in nutrition, 2020)
The study examined the long-term effects of a botanical supplement containing cinnamon, turmeric/curcumin, chromium and alpha-lipoic acid on blood glucose (BG), blood lipids and cognitive measures of healthy, older adults. Healthy, older adults aged 51 to 79 years (N = 30, 16 females, 14 males) were randomized to consume either 4 tablets/day of the active dietary supplement (1400 mg blend of cinnamon [Cinnamomum cassia bark extract], curcumin, turmeric [Curcumin Longa L. root extract and powder]; chromium and alpha-lipoic acid) or a placebo for three months in a double-blind between-subjects trial. At monthly intervals participants completed a 3.0-hour oral glucose tolerance test (OGTT). BG and blood lipids were measured at baseline and half-hour intervals, and subjects performed a battery of cognitive tests. After the two- and three-month time point there was a trend for a greater fall in BG in those taking the supplement. However, at completion of the study there were no statistically significant overall effects of supplementation on either BG levels or hemoglobin A1c. There was a positive effect of the supplement on total cholesterol and for individuals who had poorer glucose control (F(1, 16) = 12.86, P < 0.002). Results from the cognitive assessments indicated significant differences in word recall for the participants consuming the active dietary supplement (F(1, 26) = 5.74, P < 0.02). Measures of focused attention revealed significant improvements in reaction times in the group receiving the supplement (F(1, 26) = 4.48, P < 0.04). These findings suggest that the chronic ingestion of a dietary supplement containing cinnamon and curcumin/turmeric extracts, chromium and alpha-lipoic acid positively impacts blood lipids as well as aspects of cognitive performance in healthy individuals assessed during an OGTT. NeoLife International, LLC, Fremont, CA, USA.